Kyūshū Kōgyō Daigaku kenkyū hōkoku (kōgaku). Bulletin of the Kyushu Institute of Technology (Science and technology)
Vols. for 1955-1962, <1967-1973> include English abstracts of some of the papers written by faculty members of the institute which have been published in other publications.